(untitled) (One Health & Risk Management, 2025)
Introduction. The coronavirus pandemic represents one of the most significant medical crises in recent history; therefore, rapid virus detection has become a critical component of public health practice. As the virus has undergone continuous mutations, the emergence of new variants has resulted in altered transmission dynamics, changes in disease severity, and implications for diagnostic testing. Although genomic sequencing is the most effective method for mutation detection, it remains time-consuming and expensive process. Aim. To present a testing algorithm and evaluate the use of single nucleotide polymorphism (SNP) melting curve PCR for the detection of SARS-CoV-2 lineages, which may inform modifications in public health control and preventive measures, as well as potential adjustments to PCR-based diagnostic tests. Materials and methods. RNA extracted from 140 SARS-CoV-2 positive samples received in the National Reference Laboratory for Virology, at the Institute of Public Health - Skopje as part of the COVID-19 surveillance system where Ct value ≤ 25 were subjected to SNP testing. Results. Analysis of 140 SARS-CoV-2–positive samples collected between January and September 2022 using SNP testing revealed a predominance of the BA.4/BA.5 Omicron sublineages, accounting for 55.7% of cases. Conclusions. Targeted SNP assays enable rapid and accurate detection of mutations associated with specific SARS-CoV-2 Omicron sublineages, facilitating early identification of emerging variants. These results may subsequently be subjected to further investigation, ultimately contributing to an improved public health response.